1999
DOI: 10.1021/ja983905+
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Cytomegalovirus Protease by Monocyclic β-Lactam Derivatives:  Kinetic Characterization Using a Fluorescent Probe

Abstract: Recent reports have demonstrated the potential of monocyclic β-lactam derivatives as inhibitors of human cytomegalovirus (HCMV) protease. Investigation of the mechanism of inhibition by NMR and mass spectrometry has revealed the presence of an acylenzyme intermediate suggesting that β-lactams are hydrolyzed by the enzyme and cause inhibition by competing with substrate. The potential of a fluorogenic β-lactam derivative for convenient kinetic characterization of this mechanism has been evaluated using 4S-(4-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…18 Several studies in the past have shown a time-dependent inhibition of b-lactam and b-lactone compounds against Ser/His/Asp catalytic triad enzymes such as penicillin-binding proteins, 34 b-lactamases 23,35 and several Ser proteases. [36][37][38] On the basis of this precedent for other Ser/His/Asp catalytic triad enzymes, we reasoned that HTA might be inhibited by similar compounds that have the potential to form a covalent bond with the catalytic Ser (Figure 4). Furthermore, the active site and substrate binding geometry of HTA is unique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Several studies in the past have shown a time-dependent inhibition of b-lactam and b-lactone compounds against Ser/His/Asp catalytic triad enzymes such as penicillin-binding proteins, 34 b-lactamases 23,35 and several Ser proteases. [36][37][38] On the basis of this precedent for other Ser/His/Asp catalytic triad enzymes, we reasoned that HTA might be inhibited by similar compounds that have the potential to form a covalent bond with the catalytic Ser (Figure 4). Furthermore, the active site and substrate binding geometry of HTA is unique.…”
Section: Discussionmentioning
confidence: 99%
“…23 In contrast, b-lactams are reversible inhibitors of some Ser proteases. 37 In this case, the protease cleaves the b-lactams and the cleaved products compete with the substrate. HTA Hin is irreversibly inhibited by the three b-lactone compounds.…”
Section: Discussionmentioning
confidence: 99%
“…β-Lactams act also as inhibitors for thrombin [5], human cytomegalovirus protease (HCMV) [6] ( a β-herpes virus) which is a serious pathogen in immunecompromised individuals [7], matrix metalloprotease [8], cysteine protease [9] and human leukocyte elastase (HLE) [10]. Spirocyclic β-lactams have attracted attention as they have been shown to be β-turn mimetics [11] and precursors for α,α-disubstituted β-amino acids [12].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Recently, the role of β-lactam antibiotics as neuroprotectors has also been reported as they increase the expression of glutamate carriers. [8] Following the developments in the synthesis of new 2-azetidinones, their use as intermediates in organic synthesis led to the term "β-lactam synthon method" being coined by Ojima and co-workers more than 20 years ago.…”
Section: Introductionmentioning
confidence: 99%